AROMATERAPI PEPPERMINT TERHADAP MASALAH KEPERAWATAN KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS ANAK DENGAN BRONKOPNEUMONIA - Amelia, Sherly; Oktorina, Rola; Astuti, Niko (REAL in Nursing Journal, 2018)
Bronchopneumonia is an infectious disease that may be caused by morbidity and mortality in children under 5 years old. Basic Health Research survey in 2013 found that bronchopneumonia was the second cause of death in children in Indonesia. The highest incidence occurred in children at 12-23 months. It was around 21.7%. A common problem often found in bronchopneumonia is ineffective airway clearance. One way to overcome this problem is by using peppermint aromatherapy. This study aims to determine the effect of peppermint aromatherapy on ineffective road cleaning in 1-5 years old children with bronchopneumonia in Padang Panjang Hospital in 2018.The design of this research was Quasi Experiment with One Group Pretest-Posttest design. Accidental sampling techniques had been used in this reseach. Then, 10 respondents had been chosen as the samples.The data were collected trough physical examination and observation. Next, it was analyzed by Wilcoxon Sign Rank test.The results of this reseach obtained that p= 0.002 <0.05. It means that there was influence of peppermint aromatherapy on airway cleaning nursing problems in 1-5 years old children with bronchopneumonia.In short, peppermint aromatherapy can be used as a non-pharmacological therapy to overcome airway cleaning problems ineffective in pediatric patients with bronchopneumonia. Keywords: Bronchopneumonia, Ineffective Airway Clearance, Peppermint Aromatherapy